2020
DOI: 10.1016/j.revmed.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of hospitalized patients with SARS-CoV-2 infection at Toulouse University hospital (France). Results from the Covid-clinic-Toul cohort

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has spread worldwide from epicenter of Wuhan, China since December 2019. The aim of our study was to describe the clinical characteristics and outcome of hospitalized patients with SARS-CoV-2 pneumonia at the Toulouse university hospital, France. Patients and methods We selected the patients included from March 7, 2020 to April 20, 2020 in the retrolective Covid-clinic-Toul cohort that fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…Recent studies have shown that a renin-angiotensin system imbalance due to COVID-19 can exacerbate the inflammatory state and result in a more severe clinical course of the disease (Lanza et al, 2020;Sanchis-Gomar et al, 2020). Whereas in previous studies obesity was a risk factor for mortality (Docherty et al, 2020;Goyal et al, 2020;Jourdes et al, 2020;Matsunaga et al, 2020;Simonnet et al, 2020), this was not observed in our sample. This may be due to a limitation of the study, in that obesity was not directly measured by weight or body mass index, but rather was gathered from medical records, which may have ed to underreporting.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Recent studies have shown that a renin-angiotensin system imbalance due to COVID-19 can exacerbate the inflammatory state and result in a more severe clinical course of the disease (Lanza et al, 2020;Sanchis-Gomar et al, 2020). Whereas in previous studies obesity was a risk factor for mortality (Docherty et al, 2020;Goyal et al, 2020;Jourdes et al, 2020;Matsunaga et al, 2020;Simonnet et al, 2020), this was not observed in our sample. This may be due to a limitation of the study, in that obesity was not directly measured by weight or body mass index, but rather was gathered from medical records, which may have ed to underreporting.…”
Section: Discussioncontrasting
confidence: 89%
“…The overall mortality was 22.0%, which is similar to that found in studies in Spain and Italy (Borobia et al, 2020;Giacomelli et al, 2020), but higher than in studies in the US, Asia, France, Iran, Japan, Russia, Turkey, and the Democratic Republic of the Congo (Chen et al, 2020;Goyal et al, 2020;Jourdes et al, 2020;Matsunaga et al, 2020;Munblit et al, 2020;Myers et al, 2020;Nachega et al, 2020;Nikpouraghdam et al, 2020;Quisi et al, 2020;Richardson et al, 2020;Yu et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…The present study reveals a delay in seeking care after the onset of first symptoms and consultation ranging from 0.0 days to 45.0 days with a mean of 7.2 days. Despite a difference in time period and target population, other studies conducted in France and China have found a similar mean duration of approximately 7 days [ 3 , 5 , 26 ]. Data were not collected to investigate reasons for the choice of delays to seeking care after the onset of symptoms, as in other published studies.…”
Section: Discussionmentioning
confidence: 96%
“…In the study of Jourdes et al has been reported that 42. 2% of the patients in the inpatient service were transferred to the intensive care unit (10). In COVID-19 disease, patients who need intensive care follow-up are usually over 60 years old and with additional disease (11).…”
Section: Discussionmentioning
confidence: 99%